Aplicações foliares de cobre no manejo da ferrugem-asiática da soja - Bedin, Edevan (2018)
The Asian rust caused by the fungus Phakopsora pachyrhizi is one of the most serious diseases faced by soybean [Glycine max (L.) Merrill], which can reduce productivity by 80% depending on the time of the infection. An alternative for integrated diseases management is the use of mineral nutrition along with phytosanitary treatments. Thus, the objective this study was to verify whether foliar nutrition with copper (Cu), together with phytosanitary treatments interferes in the soybean reaction to Asian rust, by lignin variation in leaf tissues, reflecting soybean yield composition. The experimental design was a randomized block with four replicates. Four concentrations off Cu (0, 30, 60, 90, 120 g Cu ha -1 ) were tested in two distinct sources (cuprous oxide and copper carbonate), together with phytosanitary treatments. Evaluations were made to determine the progression of Asian rust severity, micronutrient content in leaves and grains, as well as lignin content in leaves. The yield components and productivity were also evaluated. Foliar spraying with Cu retarded the disease progression, reducing the severity of Asian rust, positively influencing grain yield, but not significantly altering yield components. The Cu contents in the soybean leaves were influenced by foliar spraying, obtaining higher concentrations of this micronutrient. The contents of the Cu increased in the grains according to the applications performed. The amount of lignin present in the leaves was significantly altered with the application of the Cu associated to phytosanitary treatments. Thus, the studied copper sources can be used as a complementary tool for the management of Asian soybean rust.